Arabidopsis thaliana Contains Both Ni(2+) and Zn(2+) Dependent Glyoxalase I Enzymes and Ectopic Expression of the Latter Contributes More towards Abiotic Stress Tolerance in E. coli - Jain, Muskan (PLoS One, 2016)
The glyoxalase pathway is ubiquitously found in all the organisms ranging from prokaryotes to eukaryotes. It acts as a major pathway for detoxification of methylglyoxal (MG), which deleteriously affects the biological system in stress conditions. The first important enzyme of this system is Glyoxalase I (GLYI). It is a metalloenzyme which requires divalent metal ions for its activity. This divalent metal ion can be either Zn(2+) as found in most of eukaryotes or Ni(2+) as seen in prokaryotes. In the present study, we have found three active GLYI enzymes (AtGLYI2, AtGLYI3 and AtGLYI6) belonging to different metal activation classes coexisting in Arabidopsis thaliana. These enzymes have been found to efficiently complement the GLYI yeast mutants. These three enzymes have been characterized in terms of their activity, metal dependency, kinetic parameters and their role in conferring tolerance to multiple abiotic stresses in E. coli and yeast. AtGLYI2 was found to be Zn(2+) dependent whereas AtGLYI3 and AtGLYI6 were Ni(2+) dependent. Enzyme activity of Zn(2+) dependent enzyme, AtGLYI2, was observed to be exceptionally high (~250–670 fold) as compared to Ni(2+) dependent enzymes, AtGLYI3 and AtGLYI6. The activity of these GLYI enzymes correlated well to their role in stress tolerance. Heterologous expression of these enzymes in E. coli led to better tolerance against various stress conditions. This is the first report of a higher eukaryotic species having multiple active GLYI enzymes belonging to different metal activation classes.